A liberdade em Hegel e seus desafios - Pereira, Luiza Andriolo da Rocha Tavares (2012)
Questions about freedom, in Hegel's terms, need to be clarified, or at least studied more diligently so that we can better understand them. Supported by this objective, the role of this study is to approach the notion of freedom in Hegel s, drawing on both works: Philosophy of Law and Philosophy of History; which are capable of coping with this true hermeneutical impasse on the notion, and even the existence of freedom. Therefore, matters that are relevant to the Hegelian philosophy, such as the necessity and contingency, it would require the use of the whole system to be interpreted - which is avoided in this study. The question of free will and ethics, for example, are closely related to the theme of freedom itself. The current democracies, on the other hand, commence to rethink the role of freedom, and it is necessary to consider it, pointing out the actuality of the Hegelian philosophy. The equality then appears as one of the greatest challenges of our time, which also implies on the approach of their own limits of freedom. To what extent does the equality restrict a freedom already guaranteed? It is also inquired, to what extent equality opposes to the liberal rights, which are based on the notion of free will and freedom itself, and which is, for Hegel, only the freedom pre-stage. The Hegelian notion of mediation is really important in this regard. Would the equality be the other side of freedom? Would it be part of it? Or would it be dependent?